CuII2, CuII4 and CuII6 complexes with 3-(2-pyridyl)pyrazolate. Structure, magnetism and core interconversion. (1st October 2019) - Das, Arup Kumar; De, Anindita; Yadav, Prerna; Lloret, Francesc; Mukherjee, Rabindranath
Graphical abstract: Synthesis of three multi-nuclear copper(II) complexes without (di) and with (tetra and hexa) benzoate bridges have been accomplished; core interconversion and magnetic studies have also been done. Abstract: Reactions of stoichiometric amounts of L 1 (−) (HL 1  = 3-(2-pyridyl)pyrazole) with [Cu(H2 O)6 ](ClO4 )2, with or without PhCO2 −, in MeOH or N, N ′-dimethylformamide (dmf), led to the isolation of three copper(II) complexes of varying nuclearity, [Cu II 2 (L 1 )2 (ClO4 )2 (MeOH)2 ] (1 ), [Cu II 4 (L 1 )4 (O2 CPh)2 (MeOH)4 ](ClO4 )2 ·2H2 O (2 ) and [Cu II 6 (L 1 )6 (O2 CPh)2 (ClO4 )2 (dmf)4 ](ClO4 )2 ·2dmf·2H2 O (3 ). Structural analysis reveals two centrosymmetric four-coordinate {Cu II (L 1 )(ClO4 )(MeOH)} units are dipyrazolate-bridged in1, giving rise to a square-pyramidal (SP; τ  = 0.13) coordination to the Cu II ion. In2, two centrosymmetric four-coordinate dipyrazolate-bridged {Cu II 2 ( μ -L 1 )2 (MeOH)2 } 2+ units in two layers are held by two syn – anti PhCO2 − bridges, giving rise to Cu II centres with a distorted SP geometry ( τ  = 0.28) geometry. In3, a three-coordinate dipyrazolate-bridged {Cu II 2 ( μ -L 1 )2 } 2+ unit is held between two {Cu II 2 (L 1 )2 (ClO4 )(dmf)2 }} 2+ units in two different layers by two syn – anti bridging PhCO2 − ligands in a centrosymmetric manner, generating two SP ( τ  = 0.03 and 0.28) and a square-planar geometry. In2, two successive layers are held by two and in3 by one PhCO2 − bridge(s). Systematic core-interconversion studies as a function of PhCO2 −, solvent (MeOH, dmf) and concentration have been done and the observed results have been rationalized. Variable-temperature magnetic studies (1.9–300 K) for powdered samples of1 –3 revealed strong antiferromagnetic coupling between the two copper(II) centres in the {Cu II 2 ( μ -pyrazolato)2 } 2+ units. For2 and3, additional magnetic interactions through PhCO2 − bridge(s) between two layers have also been realized. The magnitude of the coupling is discussed in terms of the structural parameters.